KARL SCHMITT AND HANS KELSEN’S DISCUSSION ON THE GUARANTOR OF THE CONSTITUTION IN THE CONTEXT OF THE CONFLICT OF POLITICAL AND LEGAL DOCTRINES - Anton D. Ukhanov (Вестник Московского государственного областного университета, 2022)
<!DOCTYPE html> Aim. To establish common and diverging points of Karl Schmitt’s decisionism and Hans Kelsen’s pure theory of law, which manifested themselves during the discussion on the guarantor of constitution. Methodology. The approach of the Cambridge School of Conceptual History, described in the methodological works of the political thought historian Quentin Skinner, is used as the methodological basis of the study. The key approach is complemented by the use of special methods, which include comparative, formal-legal, and historical-biographical methods. Results. It is revealed that the discussion about the guarantor of the constitution demonstrates a high degree of antagonism between the political and legal teachings of K. Schmitt and G. Kelsen. These contradictions concern not so much specific political and legal requirements (recognition of the Reich President as the guarantor of the constitution or the establishment of a constitutional court for the same purpose), but theoretical and methodological objectives and interpretations of key concepts on which thinkers base their positions, as well as the argumentative strategies that seem convincing and are used by them to defend their own points of view. Research implications. The theoretical significance lies in the establishment of the factors underlying the contradictions between the doctrines, as well as the role of discussion in the formation of each of them. At the same time, the acuteness of the disagreements revealed during the polemic problematizes the construction of the state-legal theory as a kind of integral structure. In addition to this, it seems that the propositions put forward have significant heuristic potential and, subject to further refinement, can partially be used to explain the development of the history of political and legal thought.